Symbolic Numerical Distance Effect Does Not Reflect the Difference between Numbers - Krajcsi, Attila; Kojouharova, Petia (Frontiers in Psychology, 2017)
In a comparison task, the larger the distance between the two numbers to be compared, the better the performance, a phenomenon termed the numerical distance effect. According to the dominant explanation, the distance effect is rooted in a noisy representation, and performance is proportional to the size of the overlap between the noisy representations of the two values. According to alternative explanations, the distance effect may be rooted in the association between the numbers and the small-large categories, and performance is better when the numbers show relatively high differences in their strength of association with the small-large properties. In everyday number use the value of the numbers and the association between the numbers and the small-large categories strongly correlate, thus, the two explanations have the same predictions for the distance effect. To dissociate the two potential sources of the distance effect, in the present study participants learned new artificial number digits only for the values between 1 and 3, and between 7 and 9, thus, leaving out the numbers between 4 and 6. It was found that the omitted number range (the distance between 3 and 7) was considered in the distance effect as 1, and not as 4, suggesting that the distance effect does not follow the values of the numbers predicted by the dominant explanation, but it follows the small-large property association predicted by the alternative explanations.